Establishing Tacit Knowledge Capture System in Project-Oriented Organizations Based on TOGAF Enterprise Architecture: A Systematic Review - Mandana Hayati; Saeideh Ebrahimi; Alireza Nikseresht; Mahmood Javan; Zouhayr Hayati (کتابداری و اطلاع‌رسانی)
Objective: This study seeks to investigate how to establish a tacit knowledge capture system in project-oriented organizations based on TOGAF enterprise architecture. Methodology: Due to few research studies on how to implement enterprise architecture in the framework of TOGAF in order to capture tacit knowledge in project-oriented organizations, as well as the lack of a comprehensive picture of these studies and methods used, it was necessary to make an informed decision and summarize in line with the objectives of the study, their results should be comprehensively examined. Therefore, the present study has been carried out using a systematic review method, which is one of the types of qualitative research methods that is used to investigate phenomena and identify categories based on research works, which in this research study is taken from the protocol proposed by Kitchenham and Charters. Systematic review includes three stages: planning stage, implementation stage and reporting stage. Findings: The evidence showed that "TOGAF enterprise architecture" and the related frameworks for capturing tacit knowledge as a tool for organizational knowledge management and considered it as a necessary model for the transfer of explicit and tacit knowledge. They showed that the "ADM" cycle is the most useful method and for knowledge management activities, although the preservation and use of knowledge has not been directly considered. And none of them have actually implemented all the steps of this cycle. Conclusion: The results showed the limitations related to the management of tacit knowledge in projects and emphasized the use of "TOGAF enterprise architecture" and the importance of knowing its frameworks and techniques in order to capture tacit knowledge and as a tool for managing explicit and tacit types of knowledge in organizations. And it has been introduced as a means of transferring knowledge by analyzing the "Architecture Development Method" (ADM) cycle. However, how to preserve and use knowledge has not been directly considered. The findings have considered a comprehensive system for managing information and tacit knowledge based on the organization's strategic goals and users' needs, which is the preliminary stage of the "Architecture Development Method" (ADM) cycle. They also investigated the knowledge management system of the project in a potential way and focused on the initial stages in the Enterprise architecture, but they did not implement all the steps of this cycle in a practical way. In the end, it can be said that in order to capture and store tacit knowledge of projects, TOGAF enterprise architecture framework should be used due to its global acceptance because it is considered to implement tacit knowledge management. But so far, the integration of tacit and explicit knowledge in organizational processes and how to save in order to retrieve this type of knowledge has not been directly considered. This knowledge gap has been clearly stated in the research studies. On the other hand, in none of the studies, other knowledge beneficiaries have been considered in this process, and thus the tacit knowledge of the projects has had some shortcomings.